Recovery and Increasing the Preparedness of Communities Around Mount Merapi in Facing the Spread of Volcanic Ash - Pranoto Suryo Herbanu; Ardi Ziadatul Khoir; Gilang Maulidiansah Putra; Muhamad Denis Amanda (Prospect Publishing, 2023)
In March 2023, Mount Merapi's activity increased by releasing hot clouds and producing volcanic ash (volcanic ash rain). The distribution of volcanic ash to the northwest and north in varying intensity. Furthermore, there are three villages that have the most severe impacts from the distribution of volcanic ash, namely Krinjing, Klakah, and Tlogolele Villages. Moreover, immediate action from all stakeholders is needed to minimize the impacts of the volcanic ash. In addition, a combination of all parties is also required so that it can increase community preparedness in dealing with the spread of volcanic ash. Then, the spread of volcanic ash in the future will only have a slight negative impact. In this article, the researcher used a descriptive approach as a research methodology. Data collection techniques used observation, interviews, and questionnaires, as well as Focus Group Discussion (FGD). The research sample collection method used purposive sampling with simple statistics in data analysis. In addition, the results of the FGD are also used as a result to formulate recovery priorities after the spreading of volcanic ash and strategies for increasing preparedness in dealing with volcanic ash. The data analyzed in this research also shows that the people in Krinjing, Klakah, and Tlogolele villages have a moderate level of preparedness, a score of 266 from 750 or 35.47%. Furthermore, there are four strategies for increasing community preparedness. They are 1) suggesting wearing masks when volcanic ash spreads, 2) preparing a routine budget for handling volcanic ash, 3) providing reserves for animal feed, and 4) procuring water reservoirs for each head of the family. In determining of recovering section, FGD suggests preparing the mobilization of resources, focusing on cleaning public facilities, supplying clean water, distributing masks, procuring animal feed, and socializing the dangers of volcanic ash.